2021
DOI: 10.3390/ijerph18010303
|View full text |Cite
|
Sign up to set email alerts
|

Regular Exercise and Depressive Symptoms in Korean Older Adults

Abstract: Prior studies have found that exercise has a positive effect on depressive symptoms in the general population. For older individuals, however, the association between exercise and depressive symptoms is conclusive. We examined whether regular exercise is related to depressive symptoms in 5379 Korean adults aged ≥55 years using data from a 2016 survey administered in the Korean Longitudinal Study of Aging. We used the 10-item Center for Epidemiological Studies–Depression scale to assess depressive symptoms. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…An active lifestyle, such as physical exercise or a balanced diet, could be a valid low-cost preventive strategy to counteract LLD (106). A study in South Korea suggested that it is important to encourage older individuals to exercise regularly to relieve depressive symptoms and that hand-grip strength may increase the effect of regular exercise on depressive symptoms among individuals 65 years and older (107).…”
Section: Non-pharmacological Treatment Of Lldmentioning
confidence: 99%
“…An active lifestyle, such as physical exercise or a balanced diet, could be a valid low-cost preventive strategy to counteract LLD (106). A study in South Korea suggested that it is important to encourage older individuals to exercise regularly to relieve depressive symptoms and that hand-grip strength may increase the effect of regular exercise on depressive symptoms among individuals 65 years and older (107).…”
Section: Non-pharmacological Treatment Of Lldmentioning
confidence: 99%
“…47 Kim et al examined the relationship between regular exercise and depressive symptoms in 5,379 Korean adults aged !55 years. 48 The results revealed a significant association between a lack of regular exercise and increased frequency of depressive symptoms in older adults. In addition, hand grip strength may increase the effect of regular exercise on depressive symptoms in individuals aged 65 years and older.…”
Section: Exercise and Depressionmentioning
confidence: 87%